Possession or Sharing - The New Rules of Property Management in Profit Making - Scheibe, Anna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the new rules of property management in profit making. The author analyse the notion of the property and its meaning for the profit creation process, changes in the contemporary business environment and creating competitive advantage in new conditions on the example of the use of intellectual property rights, property and profits in the new reality.